Classical Enteropathy-Associated T-cell Lymphoma (EATL) Complicating A Crohn’s Disease Patient on Thiopurine Monotherapy: A Case Report - Rozi, Nur Raziana; Jaafar, Khairul Azhar; Kori, Ahlam Naili; Che Aun, Azlida; Md Salleh, Nor Hafliza (IIUM Medical Journal Malaysia, 2022)
Thiopurine exposure from inflammatory bowel disease (IBD) treatment had been associated with a higher risk of lymphoproliferative disorders namely peripheral T-cell lymphoma, as early as 2 years after its initiation. We report a rare case of classical or type 1 enteropathy-associated T-cell lymphoma (EATL) with liver metastasis in a long-standing Crohn’s disease 61-year-old patient treated with azathioprine monotherapy. He presented with acute, severe abdominal pain with cholestatic jaundice and pancytopenia. Colonoscopy showed multiple small, superficial ulcers at the terminal ileum and the biopsy taken was reported as classical EATL, an uncommon gastrointestinal non-Hodgkin’s lymphoma with CD2, CD 3, CD 30, and CD 56 positivity and more than 90% Ki67 proliferative index. Computed tomography (CT) 3-phase liver scan suggested liver metastasis. This case highlights the unusual presentation of classical EATL in non-celiac disease patients and its risk association with thiopurine therapy in IBD.